Optimization of supercritical carbon dioxide extraction parameters of cocoa butter analogy fat from mango seed kernel oil using response surface methodology - Akanda, Md. Jahurul Haque; Sarker, Md. Zaidul Islam; Nik Ab Rahman, Nik Norulaini; Ferdosh, Sahena; Rahman, Md. Mokhlesur; Mohd Omar, A.K. (Association of Food Scientists & Technologists, 2015)
Mango seed kernels (MSK) are discarded as agricultural wastes of industrial processing’s by-product as well as direct consumption of the mango fruits. The extraction parameters of SC-CO2 were optimized using central composite design (CCD) of response surface methodology (RSM) yielding cocoa butter analogy fats from MSK. The pressure, temperature, and CO2 flow rate were considered as variables, where the linear and quadratic effect of the flow rate of CO2, quadratic effect of pressure, and interaction between pressure and temperature was positive and most significant on the MSK oil yield. On the other hand, linear effect of pressure and temperature, quadratic effect of temperature, and interaction between temperature and CO2 flow rate had a less impact. The optimized oil yield was predicted to be 11.29 % at 44.2 MPa, 72.2 °C and CO2 flow rate of 3.4 ml/min which was close to the oil yield (11.7 %) of Soxhlet extraction method. However, the stearic (41.99 to 42.21 %) and oleic (43.78 to 43.89 %) the predominant fatty acids in terms of triglycerides constituents were found in MSK oils extracted by SC-CO2 and Soxhlet methods. The MSK oil extracted using SC-CO2 method could be regarded as premium quality cocoa butter analogy fats in this study.